2015
DOI: 10.1039/c5tb01150g
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of an indazole ligand into the self-polymerization of dopamine for enhanced binding with metal ions

Abstract: Synthesis and mussel-inspired polymerization of a new catechol monomer. The generated copolymer exhibits enhanced metal binding, due to the ligand nature of the new monomer, compared to polydopamine homopolymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…Oxidation of 5,6‐dihydroxy‐1H‐indazole as an aza‐analogue of DHI by air in Tris buffer led to a dark material useful for the coating of silica particles and the production of polymeric capsules after removal of the silica core (Scheme ) . The polymerization was slower than in the case of DA polymerization.…”
Section: Pdanas By Oxidative Polymerization Of Da Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidation of 5,6‐dihydroxy‐1H‐indazole as an aza‐analogue of DHI by air in Tris buffer led to a dark material useful for the coating of silica particles and the production of polymeric capsules after removal of the silica core (Scheme ) . The polymerization was slower than in the case of DA polymerization.…”
Section: Pdanas By Oxidative Polymerization Of Da Derivativesmentioning
confidence: 99%
“…Oxidative copolymerization of DA with N‐substituted DA (top), 5,6‐dihydroxyindazole (middle) and 5‐hydroxyindole (bottom) …”
Section: Pdanas By Copolymerization Of Da With Other Monomers or Reacmentioning
confidence: 99%
See 1 more Smart Citation
“…A concerted effect of redox reactions, redox‐dependent differential cation binding affinity and nanoscale architecture collectively facilitates the insertion and removal of multivalent cations in melanin. Fan et al reported that the copolymerization of 5,6‐dihydroxy‐1H‐indazole with dopamine will enhance the binding with metal ions . The 1:3 copolymer (indazole‐to‐dopamine ratio) has adequate structural stability as a polymer coating.…”
Section: The Modulation Of Melanin‐like Materialsmentioning
confidence: 99%
“…The corresponding nitroindazole-pyrazoline derivatives were obtained in good to excellent yields.Molecules 2020, 25, 126 2 of 18 antipyretic, antioxidant, antiparasitic, antimicrobial, antitumoral and anti-inflammatory activities, among others [5][6][7][21][22][23].Indazoles are another important group of N-heterocycles with significant biological activities as nitric oxide synthase (NOS) inhibitors, kinase inhibitors, anti-inflammatory, anticancer, antimicrobial, antifungal, antimalarial, and antileishmanial agents, among others.Some anticancer and anti-inflammatory drugs based in indazole scaffolds are commercially available [24][25][26][27][28][29][30]. Besides the biological properties presented by indazole derivatives, this family of N-heterocycles also showed potential to be used in other fields as corrosion inhibitors, components for OLEDs and battery applications, and as copolymerizing molecules for new materials [31][32][33][34].Following our interest on developing synthetic approaches to functionalize the indazole core [35,36], we decided to follow the 1,3-dipolar cycloaddition methodology to substitute nitroindazoles with triazole or pyrazoline moieties, aiming in such way to obtain new compounds with improved biological features for different applications. In the strategy envisaged it was considered that the alkylation of indazole with 1,2-dibromoethane using liquid-liquid phase transfer catalysis, could afford not only the N-1and N-2-bromoethylindazoles, but also the corresponding N-1and N-2-vinylindazoles [37].…”
mentioning
confidence: 99%